Application Of Digital Brochure Design In Optimizing Promotional Activities At Al-Amalul Khair Islamic Boarding School: Penelitian - Ulfah Muharramah; Heni Yuvita; Andriansyah; Dika Setiagraha; Subashnee A/P Marimuthu; Annisa Balqis; M Febriansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service initiative was designed to address digital promotion challenges at Al-Amalul Khair Senior High School through the comprehensive implementation of a redesigned digital brochure. The program adopted a systematic approach encompassing four key phases: coordination and needs assessment, digital brochure implementation, monitoring and evaluation, and scholarly publication. Primary activities included field surveys, brochure design using digital platforms, collaborative content review sessions, and digital distribution of the final materials. The project yielded significant outcomes, including the successful completion of both the brochure redesign and an instructional guide for utilizing digital design platforms. Stakeholder feedback indicated substantial improvements in visual appeal, information clarity, and promotional effectiveness. Teachers appreciated the more organized information presentation, while students found the core promotional message more focused and accessible. International collaboration with Politeknik Merlimau Melaka further enriched the project by providing valuable cross-cultural perspectives on infographic design and color scheme selection. This initiative has not only transformed the school's promotional strategy but also fostered digital capacity development, effectively bridging traditional educational values with contemporary digital marketing requirements while creating sustainable opportunities for advancing digital literacy.